1-Aminocyclopropane-1-Carboxylate Deaminase-Producing Plant Growth-Promoting Rhizobacteria Improve Drought Stress Tolerance in Grapevine (Vitis vinifera L.) - Duan, Bingbing; Li, Lin; Chen, Guoqiao; Su-Zhou, Chenxing; Li, Yashan; Merkeryan, Hasmik; Liu, Wei; Liu, Xu (Frontiers in Plant Science, 2021)
Plant growth-promoting rhizobacteria (PGPRs) that produce 1-aminocyclopropane-1-carboxylate (ACC) deaminase are capable of reducing limits to plant growth due to water-deficient conditions. Here, seven PGPR strains that can produce ACC deaminase were successfully obtained from the rhizosphere soil of grapevine (Vitis vinifera L.) in arid regions of China. The strains belonged to three different genera: Pseudomonas, Enterobacter, and Achromobacter, according to their 16S rDNA sequencing analysis. A drought tolerance experiment revealed two PGPR strains (DR3 and DR6) with exceptionally high phosphate solubilization, nitrogen fixation, indoleacetic acid (IAA), and exopolysaccharides secretion potential. Both strains were selected for use in a pot experiment to evaluate their growth-promoting effects on grapevines under drought conditions. Each of these two PGPRs and their mixed inoculation into grapevines were expected to alleviate the comprehensive growth inhibition of grapevines caused by drought stress. The mixed inoculation was hypothesized to elicit the best growth-promoting effects. Inoculation with the PGPRs not only enhanced the root-adhering soil/root tissue ratios and soil aggregate stability, but it also increased the nitrogen and phosphorus levels in the soil and plant leaves. Further, inoculation with PGPRs significantly altered the plant height, biomass of shoot and root organs, relative water contents, and net photosynthetic rate of leaves, enabling grapevines to better cope with drought. Moreover, the contents of IAA, abscisic acid, and malondialdehyde in these grapevines under drought stress were significantly changed by PGPRs. They indirectly affected biochemical and physiological properties of grapevines to alleviate their drought stress. Taken together, these results demonstrate that the DR3 and DR6 PGPRs might be useful for effectively weakening the growth inhibition caused by drought in grapevines. The strains might also be applied as effective bioinoculants to maintain the quality of wine grapes.